Molecular surveillance of dengue virus in Bahia State, Brazil - Melo, Paulo R.; Domingo, Cistina; Santos, Stênio C.; Cerqueira, Bruno A.; Andrade, Luis J.; Nunes, Juliana B.; Ciuffo, Isolina A.; Tenório, Antônio; Blanton, Ronald E.; Reis, Mitermayer G. (Scientific Research Publishing, 2012)
Dengue is an important emerging viruses, posing a threat to one-third of the global human population. In 2002, the introduction of DENV-3 in the state of Bahia produced massive epidemic (about 35,000 cases detected) and the first cases of dengue hemorrhagic fever. To understand the nature of the virus circulating at Bahia, E/NS1 sequence was determined for 31 DENV viruses isolated in Bahia during the 2006 and 2007 transmission season, from patients presenting with different degrees of severity. The carboxi-terminal region of the E gene (220 nt) of 31 viruses, isolated from dengue patients with clinical diagnosis of dengue infection were used to determine the genetic variability of dengue 2 (DENV-2) and dengue 3 (DENV-3). Sequence data were used in phylogenetic comparisons with global samples of DENV-2 and DENV-3. DENV-2 sample grouped in the South East Indian genotype, while DENV-3 samples were grouped within Indian genotype. This study is the first report on Bahia isolates during two transmission seasons. Our data confirms reports from other parts of Brazil and different countries showing the DENV-3 (geno-type III) strains circulating in the Americas are closely related, and cluster within the genotype that has been associated with DHF epidemics in different conti-nents.
Keywords: Dengue; Dengue Hemorrhagic Fever; Molecular Surveillance; DENV Genotypes; E/NS1Junction